SAT0307 Treat to Target of Psoriatic Arthritis: Core Set Criteria of Minimal Disease Activity. (23rd January 2014) - El Miedany, Y.; El Gaafary, M.; Youssef, S.; Ahmed, I.; Nasr, A.; Palmer, D.
Abstract : Background: Recently, the concept of "treat-to-target" has emerged as a topic of great interest in rheumatology, particularly as regards the therapeutic approach to RA patients. PsA is a multifaceted disease that may involve arthritis, skin and nail disease, enthesitis, dactylitis and axial disease. There are no agreed composite outcome measures for PsA that assess all of these differing disease manifestations. Objectives: To identify a validated core set of definitions that are able to recognise patients who achieved optimal therapeutic outcomes and reached minimal disease activity (MDA) levels. Methods: The conceptual definition of MDA approved at the OMERACT- 6 conference was agreed as a core set of domains for PsA. This includes: Peripheral joint activity measured using the 68 tender/66 swollen joint count, Skin activity assessed using both PASI score and Body surface area (BSA), back pain, joint pain, duration of morning stiffness and patient's global assessment of disease activity measured using 100 mm VAS scales. The modified HAQ was used as a measure of physical function and enthesitis count was included with a maximum value of 13. In addition, ESR and CRP were assessed. Dactylitis was scored as a swollen joint. An interdisciplinary group of physicians, nurses and patients considered that patients who receive DMARDs and/or biologic therapy who achieved 90% improvement of their outcome measures supported by no activity as shown on US assessment (both on Grey scale and Power Doppler examination) of the joints and enthesis sites and feel able to go back to work would be considered in remission and included in this work. Every patient completed a PROMs questionnaire at baseline and prior to every clinic visit [1 ]. Results: 143 PsA patients were assessed in a multicenter study. Aiming for high specificity to reduce false positives, 5 domains were identified as core set criteria in PsA patients: Spine, Joints, Skin, Enthesis and functional disability. A patient is classified as achieving MDA when: Spine: ASDAS < 1.3; Joints: tender joint count ≤1 and swollen joint count ≤1; PASI ≤1 or BSA ≤3; Functional disability ≤0.5/3; tender entheseal points ≤1. Comparing the outcome measures of the cases who achieved MDA to their pre-treatment scores, revealed a significant difference (P<0.01) between the values for all of the domains. Individual regression analysis showed that all domains were predictors of MDA. Based on the mean cut-off points the suggested 5 domains achieved sensitivity 92%, specificity 96%. Conclusions: Aiming for low levels of disease activity can improve the outcome of PsA patients. This study provides a global definition of an MDA "state" in PsA and defines a target for treatment. It is based on current expert opinion and patients and uses a composite of key outcome measures in PsA including US to encompass all of the domains of the disease. References: El Miedany et al. Joint Bone Spine 2010; 77: 575-581 Disclosure of Interest: None Declared